2018
DOI: 10.1038/s41598-018-31434-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of short-term exposure to ambient carbon monoxide with hospital admissions in China

Abstract: Evidence on the acute effects of ambient carbon monoxide (CO) pollution on morbidity risk in developing countries is scarce and inconsistent. We conducted a multicity case-crossover study in 26 largest cities in China from January, 2014 to December, 2015 to examine the association between short-term exposure to CO and daily hospital admission. We fitted conditional logistic regression to obtain effect estimates of the associations. We also performed subset analyses to explore the health effects of CO at low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
9
16
0
Order By: Relevance
“…Moreover, associations between ambient CO and cardiovascular mortality had further been confirmed in a nationwide time-series analysis in 272 cities in China [ 7 ] and in the China Air Pollution and Health Effects Study (CAPES) [ 13 ]. Our results were consistent with previous studies performed in different Chinese cities [ 7 , 13 , 14 , 35 ] that reported a significant CO exposure effect on lag 0 and lag 1 day, and a maximum CO exposure effect on lag 0–1 day. Another recent study conducted in Beijing showed similar findings compared to our results [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, associations between ambient CO and cardiovascular mortality had further been confirmed in a nationwide time-series analysis in 272 cities in China [ 7 ] and in the China Air Pollution and Health Effects Study (CAPES) [ 13 ]. Our results were consistent with previous studies performed in different Chinese cities [ 7 , 13 , 14 , 35 ] that reported a significant CO exposure effect on lag 0 and lag 1 day, and a maximum CO exposure effect on lag 0–1 day. Another recent study conducted in Beijing showed similar findings compared to our results [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…PCA is a multivariate method and has been applied in various multipollutant studies. Our current findings were consistent with those of previous studies exploring the association between CO exposure and the risk of hospital admissions for CVD after adjusting for PM 2.5 , NO 2 , SO 2 and O 3 [ 7 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations